Intervening against the Fed - Alexander Rodnyansky; Yannick Timmer; Naoki Yago (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the spillovers of US monetary policy and the mitigating role of foreign exchange interventions (FXI) by combining deviations from a daily FXI policy rule with high-frequency US monetary policy shocks, daily exchange rates, and firm-level stock prices, as well as firm-level balance sheet variables across several countries. We first present evidence that–without interventions– contractionary US monetary policy shocks spill over through a balance sheet channel: foreign exchange rates depreciate and stock prices fall, driven by those firms with US dollar debt. However, when countries counter-intervene, the spillover of US monetary policy tightening is muted. FXIs entirely offset the depreciation of the domestic exchange rate and the reduction in stock price for firms with US dollar debt, suggesting that "intervening against the Fed" protects economies from the adverse spillover of US monetary policy tightening through the balance sheet channel of exchange rates.
Keywords: E44; E52; F31; F32; F41; 330; foreign exchange intervention; monetary policy spillovers; balance sheet channel; exchange rates; dollar debt